(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we first introduce the irreducible unitary representation of nilpotent Lie groups, then by using the irreducible unitary representation we construct a fundamental solution to a class of left invariant differential operators and thus obtain the global solvability of this kind of operators.